The Effect of Health Education Programs on Adolescents’ Knowledge and Attitudes regarding Reproductive Health - Siswari Yuniarti; Brivian Florentis Yustanta; Intan Novita Kowaas; Annisa Nurrachmawati; Sylvina Rahmawati (Journal of World Future Medicine, Health and Nursing, 2024)
Adolescent reproductive health is an important issue in the field of public health, because adolescents are vulnerable to the risk of reproductive health problems if their knowledge and attitudes towards reproductive health are inadequate. Health education programs have the potential to improve adolescents’ knowledge and attitudes about reproductive health, but there has not been much research that thoroughly explores the impact of these programs. This study aims to evaluate the effect of health education programs on adolescents’ knowledge and attitudes about reproductive health. This research uses a quantitative research method with a pre-test post-test control experimental research design. Data on adolescent knowledge and attitudes about reproductive health were collected using questionnaires before and after the intervention. The results of this study show that after participating in a health education program, adolescents’ knowledge about reproductive health increased compared to not participating in the education program. In addition, there was an increase in teenagers’ positive attitudes towards reproductive health after participating in the educational program. This research also shows that health education programs are effective in increasing teenagers’ knowledge and attitudes about reproductive health. This emphasizes the importance of integrating reproductive health education programs in educational curricula for adolescents to increase their awareness of reproductive health issues and encourage healthy behavior. The conclusion of this research is that health education programs have a positive influence on teenagers’ knowledge and attitudes about reproductive health. This emphasizes the importance of integrating reproductive health education programs in the education curriculum to increase teenagers’ understanding and attitudes towards reproductive health issues. Collaborative efforts between educational institutions, public health and communities are needed to create an environment that supports overall adolescent reproductive health.